“E-Government” di Indonesia: Menuju Visi X “Masyarakat Telematika Berbasiskan Pengetahuan” Tahun 2020 - Teguh Ratmanto (MediaTor (Jurnal Komunikasi), 2006)
After the The Reformation Era had forced New Order steep down, the Government began a new era and introducing concept of “Clean Government” which is implemented in E-government. The Internet had helped the government to open himself for publik by online service. The Government had released declaration (Keppres No. 61/2001) which encouraged the use of Information and Communiation Technology, concerning political and legal base for the development of e-government. According to the Keppres Number 6/2001 the government had introduced TKTI (Tim Koordinasi Telematika Indonesia) which has to develop National Information Technology Framework (NITF) with a vision to establish Telematic society based on knowlede in 2020. The problems are the low of internet acces and cultural obstacles. The government, actualy , is on the right track, however they are still in the third category (Minimal e-government capacity) where almost all of sites contain only information.